Bacterial Diversity in Flores Sea Surface Water Revealed by Reanalysis of Public Shotgun Metagenomic Data - Mardalisa Mardalisa; Nursyirwani Nursyirwani; Nabila Afifah Azuga; Lilies Handayani (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
The Flores Sea in eastern Indonesia is a marine biodiversity hotspot within the Wallacea region, yet its bacterial community remains largely unexplored. This study aimed to characterize bacterial diversity in Flores Sea surface water by re-analyzing publicly available metagenomic data. Public shotgun metagenomic data was obtained from the NCBI Sequence Read Archive (SRA) under accession number SRR37631993 (Bioproject: PRJNA1437532), comprising 40,285,030 paired-end reads (2×150 bp) generated using the MGI DNBSEQ G50 platform. Quality trimming was performed using fastp v1.1.0. Taxonomic classification was conducted using Kraken2 v2.1.3 against the standard database (k2_standard_08gb_20230605), followed by species-level abundance estimation with Bracken. Diversity indices (Shannon, Simpson) were calculated based on relative abundance. The results showed that 13,041,976 reads (64.8% of total) were successfully classified, identifying 4,477 bacterial species with significant abundance. The Shannon diversity index (H') was 3.95, indicating very high diversity. The Simpson index (1-D) was 0.94, demonstrating high community evenness. The bacterial community was dominated by halophilic bacteria, with Halomonas meridiana as the most abundant species (19.7%), followed by Chromohalobacter salexigens (5.1%) and Idiomarina loihiensis (4.9%). The dominance of halophilic bacteria reflects adaptation to the marine environment. These findings provide the first baseline data on bacterial diversity in Flores Sea surface water based on a single public metagenomic sample, establishing a foundation for future microbial monitoring in the understudied Wallacea region.